Ruptured pulmonary hydatid cyst presenting as hemoptysis in TB endemic country: A case report. (June 2022) - Pangeni, Raju Prasad; Regmi, Pradeep Raj; Khadka, Sulochana; Timilsina, Bibek
Abstract: Introduction: Hydatid disease is a major zoonotic disease. After the liver, the lungs are the common site of involvement. Clinical manifestations of the disease depend on the site and size of the cysts as well as the presence of complications. The majority of the cases remain asymptomatic. Complicated pulmonary cysts can present as chest pain, cough, shortness of breath, and hemoptysis. Sometimes, imaging is not sufficient for diagnosis and histopathological evaluation can provide the confirmatory diagnosis. Case presentation: A 32-year-old female presented with the complaints of episodic hemoptysis for the duration of two years. Radiological imaging could not provide a confirmatory diagnosis. Bronchoscopy was planned further. An endobronchial biopsy was taken for histopathological evaluation after seeing the whitish membranous structure within the right middle lobe bronchus. Hence, the diagnosis of ruptured cystic pulmonary hydatidosis was made. Clinical discussion: Echinococcus granulosus is the cause of cystic pulmonary hydatid disease which is transmitted through contamination by the infected definitive host, mostly dogs. Most cases remain asymptomatic for a long period. Hydatid disease has many clinical and radiological forms which should be recognized and included in the differential diagnosis of many pulmonary problems. Sometimes, imaging and serological studies may not confirm the diagnosis, histopathological evaluation may be required. Conclusion: Uncomplicated hydatid cysts are most commonly diagnosed incidentally in the adult population. Complicated hydatid cyst can present with various clinical manifestations. Episodic hemoptysis is one of the manifestations in our case. Clinicians should be aware of the typical as well as atypical manifestations of pulmonary hydatid disease. Highlights: Ruptured pulmonary hydatid cyst usually presents with anaphylactic reaction but hemoptysis alone can be a presentation. Imaging and histologic findings help in confirming the diagnosis. Preventive educational program and early identification with atypical features are vital to prevent potential complications.